COVID-19 and the Case for Medical Management and Primary Care - Luis W. Dominguez; Joel S. Willis (SAGE Publishing, 2020)
Hospitals and health systems suffer an over-reliance on elective surgeries to remain profitable. As a result, systems report record losses, while demand for emergency room, hospital, and intensive care beds have surged. Studies have admitted that many surgeries are unnecessary, and physician leaders admit that profit plays a role in driving such needless cost and risk. Most diseases are better managed with medications and lifestyle changes. But it pays more to replace a knee than to prevent that replacement. We must bring surgical and medical value closer in-line. Communities of color are suffering disproportionately from coronavirus. The social determinants of health that lead to higher concentrations of hypertension and diabetes can be mitigated by investment in primary care. Such investment has been proven to decrease cost and increase quality of life. However, the United States spends 50% less on primary care, than other developed countries. While showing promise, telehealth is not a panacea. It relies on continued reimbursement parity, and there remains a digital divide. Any meaningful fix will draw the ire from those who profit from such a profligate system. If we want to improve quality, access and equity, while avoiding unnecessary hospitalizations, risky surgeries, and runaway costs, we must invest in primary care.